Inovasi E-Modul Berbasis Aplikasi Kvisoft Flipbook Maker Pada Pembelajaran Bangun Datar Kelas V SD - Ade Putri Nababan; Selsa Simanungkalit; Aribah Capah; Khofifah Indah T; Karina Br Sitorus (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to develop and test the feasibility and effectiveness of the Kvisoft Flipbook Maker application-based learning e-module on Build Flat material for grade V elementary school students. This research uses the Research and Development (R&D) method with the Borg and Gall development model which is modified into seven stages, including data collection, product design, validation, revision, limited trial, follow-up revision, and dissemination and implementation. The research subjects consisted of grade V students of SD Negeri 174552 Tambunan Balige (trial) and SD Negeri 104607 Sei Rotan (implementation). Validation was carried out by material experts and media experts with percentage results of 84% and 80%, respectively, which showed the "feasible" category. The results of the trial of 26 students showed an overall feasibility level of 80%, with the usefulness aspect obtaining the highest score (83%) and the lowest motivation aspect (77%). The effectiveness of the e-module was tested through the analysis of the N-Gain Score, with an average result of 0.57 (57.29%), included in the "effective" category. These findings show that Kvisoft Flipbook Maker-based e-modules are feasible and effective in mathematics learning, because they are able to increase concept understanding, learning motivation, and students' independence in learning flat building materials.